A geospatial approach to assessing land change in the built-up landscape of Wa Municipality of Ghana. Issue 2 (3rd July 2019) - Kpienbaareh, Daniel; Oduro Appiah, Joseph
ABSTRACT: Urban landscapes are changing in response to changes in socio-economic conditions. Land change scientists seek to understand these land dynamics in the coupled human-environment system of urban landscapes. This study assessed land change in the built-up area of Wa Municipality between 1986 and 2016 using Landsat images. We used the Support Vector Machine algorithm for classifying the images. We recorded image classification accuracies of 97%, 95%, 92% and 96% for the 1986, 1996, 2006 and 2016 classified images, respectively. Our study finds that over the 1986–2016 period, agricultural land and bare land transitioned to build-up land by 9.23% and 3.79%, respectively, as compared to 2.79% for vegetation and 0.05% for water. Our in-municipal level analysis thus shows that urban landscapes could expand more sustainably by targeting other dominant land categories instead of the vegetation cover. The findings in this paper could serve as a spatial model for planning and reducing the unintended socio-ecological impacts of expansion in the built-up area.